Kinetics of Isophorone Synthesis via Self‐Condensation of Supercritical Acetone. Issue 10 (16th August 2016) - Mei, Jun; Chen, Zhirong; Yuan, Shenfeng; Mao, Jianyong; Li, Haoran; Yin, Hong
Abstract: A kinetic study on isophorone synthesis via self‐condensation of supercritical acetone catalyzed by aqueous KOH in a tubular flow reactor was conducted. The intention was to improve the isophorone selectivity, with the main approach to reduce the by‐products higher‐boiling than isophorone. A higher isophorone selectivity was obtained with increased reaction temperature. The structures of main products were determined by gas chromatography‐mass spectrometry and nuclear magnetic resonance analysis. The key reaction pathways and a corresponding kinetic model were proposed. The fitted apparent activation energies indicated the reason of isophorone selectivity improvement in that high temperature favors reversion of reversible by‐products. Abstract : In a kinetic study, isophorone synthesis by self‐condensation of supercritical acetone catalyzed by aqueous KOH in a tubular flow reactor is investigated. Two isophorone selectivity indicators were introduced to evaluate the effect of temperature. Higher reaction temperatures led to improved isophorone selectivity and favored the reversion of reversible by‐products.